Change the Business Gas Station in Nakhon Ratchasima Province - แสงวิเศษ สุทธิพงษ์; ศรีราชเลา มนตรี; พาณิชย์กุล บุญช่วย (Ratchaphruek Journal, 2019)
"Energy" is one of the key factors in driving economic growth and energy production in the face of increased competition. This research is a qualitative research and a mixed-format study model. Quantitative research. Quantitative Research is the purpose of research to study the transformation of gas stations into new cultures. The research found that The pre-1997 service stations and the role of the gas station before 1997 found the product. And services. Factors contributing to the transformation of the gas station into a new culture. Social factors And the changes in values. Transforming the corporate culture into a new gas station Encountered changes in corporate culture, social and organizational culture changes.